Are Number of Passes Related with Complications in Pediatric Native Kidney Biopsies? - Mehmet Coşkun; Şeyma Akkuş; Şükran Keskin Gözmen; Malik Ergin; Erkin Serdaroğlu; Nida Dinçel (Galenos Publishing House, 2021)
Objective: The aim of this study was to determine the relationship between number of passes and complications in pediatric native kidney biopsies performed under ultrasonography guidance. Methods: Forty-nine children who underwent native kidney biopsies using a 16 Gauge semi-automatic needle between 03/2019-03/2020 were included in the study. All patients were evaluated with ultrasonography before and after biopsy procedure to detect complication(s). Two or more passes were performed in most cases where electron microscopy was required. Requirement for transfusion or intervention was considered as a major complication. The technical success was calculated considering number of glomeruli harvested. Number of passes were compared with complication rates and number of glomeruli sampled. In statistical analysis, chi-square, t-test, and ANOVA tests were used. Results: Minor, major complications and technical success rates were 36.7%, 0% and 100%, respectively. Number of passes were 1 in 4, 2 in 30, 3 in 11 and 4 in 4 cases. Increasing number of passes were related with higher complication rates (p=0.002). The complication rates were 23.5%, and 66.7% when ≤2, and ≥3 passes were used. Complication rate was higher when ≥3 passes were used (p=0.009), without any increase in the number of glomeruli sampled (p=0.839). Conclusion: Pediatric native kidney biopsy was a safe procedure using 16 Gauge needle under ultrasonography guidance. Three of more passes caused an increase in minor complication rates without any increase in the number of glomeruli sampled.